Exhaust pressure LPV observer for turbocharged diesel engine on-board diagnosis. Issue 24 (2018) - Dubuc, Donatien; Sename, Olivier; Bresch-Pietri, Delphine; Halle, Adrien; Gauthier, Christophe
Abstract: This paper deals with the estimation of the exhaust manifold pressure for a truck diesel engine equipped with a turbocharger. The knowledge of this variable is essential in order to fulfill functions such as the exhaust brake control or on-board diagnosis (OBD) of antipollution systems. However, while in most cases the pressure is directly measured, the sensor may encounter failures in some specific operating conditions. Its estimation is then of great interest for diagnosis and fault tolerant control objectives. Based on mean value models of the turbocharger and the exhaust manifold, a Linear Parameter Varying (LPV) polytopic observer is designed to provide an estimation of the pressure. The merits of this solution are illustrated with the high-fidelity professional simulator GT-POWER.